Feasibility of a structured assignment sheet by ratifying socrates and rene descartes statements on the sub-material of factors that influence reaction rate - Umi Luthfiyah; Suyono Suyono (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
The purpose of this study resulted in a Structured Assignment Sheet (SAS) on sub-material factors influential on the rate of reaction that ratified the statements of Socrates & Rene Descartes. The Structured Assignment Sheet is associated with SAS-RSRS. Eligibility criteria include validity, effectiveness, and practicality. SAS-RSRS development uses research and development (R&D) methods. The trial was conducted on a limited basis to students at Y Lamongan High School with a total of 15 people. The research instruments used to consist of validation sheets, skill test sheets ratifying Socrates & Rene Descartes statements, and student response questionnaire sheets. Data is analyzed in a quantitatively descriptive manner. SAS-RSRS is declared to meet the criteria for validity if the Mo value ≥ 4 for each problem and R ≥ 75%. SAS-RSRS is declared to meet the effectiveness criteria if the N-gain score is ≥ 0.7. It is said to meet the criteria of practicality if the percentage of student response results is ≥ 61%. The SAS-RSRS developed was declared to have qualified eligibility reviewed from validity, effectiveness, and practicality criteria.